2021
DOI: 10.1016/j.jmpt.2021.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Use of Telehealth and Face-To-Face Chiropractic Care in the Department of Veterans Affairs Before and After the COVID-19 Pandemic

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…37,38 Telehealth alternatives have been found to be generally effective, however there are signs of declining use and a return to inoffice delivery of non-pharmaceutical services. [39][40][41][42][43][44] The aim of this study was to explore how the COVID pandemic impacted care-seeking for, and the management of, LBP in commercially insured (CI) and Medicare Advantage (MA) cohorts.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
“…37,38 Telehealth alternatives have been found to be generally effective, however there are signs of declining use and a return to inoffice delivery of non-pharmaceutical services. [39][40][41][42][43][44] The aim of this study was to explore how the COVID pandemic impacted care-seeking for, and the management of, LBP in commercially insured (CI) and Medicare Advantage (MA) cohorts.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
“…There have been no reports of the rates of VHA chiropractic care use among VHA healthcare users by sex, whereas estimated rates of use by sex for the entire US population range from 5.7-11.1% for females and 4.6-9.4% for males [15,16]. Analyses of the patient population seen in VHA chiropractic clinics have reported 15.8-17.1% are female [13,17]. While a lower percentage can be expected due to the overall sex distribution within VHA, this is in contrast with the population of US chiropractic private practice patients, of which approximately 60% are female [ 1 8, 19,20].…”
Section: Introductionmentioning
confidence: 99%
“…During the COVID-19 pandemic, there was a trend of increased telehealth use. 7 , 8 , 9 , 10 The Centers for Disease Control and Prevention studied and encouraged the use of telehealth for social distancing and continuity of care purposes. 11 However, socioeconomic and rural/urban disparities continued to predominate.…”
Section: Introductionmentioning
confidence: 99%
“… 25 , 26 , 27 Currently, the literature on chiropractic and telehealth consists of descriptive works. 8 , 28 , 29 Large-scale studies looking at which types of patients receive telehealth chiropractic care (TCC) vs others have not yet been performed. A study assessing trends in VHA chiropractic telehealth visits 8 showed an increase in telehealth use to meet the demand for continuity of care early in the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation